Baculovirus-encoded protein expression for epigenomic profiling in Drosophila cells. - Bryson, T.D.; Weber, C.M.; Henikoff, S. (Fly, 2010)
The expression and genome-wide mapping of epitope-tagged DNA- and chromatin-binding proteins in cultured cells has become a powerful strategy for epigenome characterization, especially in Drosophila, where cell lines derived from numerous tissues are now available. However this strategy relies on establishing transfected cell lines, which is time-consuming and introduces variability. Here we show that baculovirus-encoded proteins can be efficiently produced following infection of Drosophila cell lines of different types. Using chromatin affinity purification, we show that epitope-tagged proteins produced in baculovirus-infected cells provide genome-wide profiles of the histone variant H2Av that are comparable to those produced by plasmid-transfected cells. The ability to express multiple epitope-tagged proteins for epigenome analysis from a single culture, and to do this in a variety of Drosophila cell lines, significantly extends the range of epigenome analysis.